Preferensi Konsumen Terhadap Pembelian Sayuran Organik Di Kota Surakarta Pada Masa Pandemi Covid-19 - Mayang Angling Arum Sari; Ernoiz Antriyandarti; Refa’ul Khairiyakh (Paspalum: Jurnal Ilmiah Pertanian, 2022)
The Covid-19 pandemic has led to increased public awareness to change their lifestyle to be healthier. As a result, people are becoming more selective in consuming vegetables, so they choose to consume organic vegetables, which are considered safer. The purpose of this study is to examine the effect of variables such as age, income, education level, the number of family members who have been infected with Covid-19, and close people who have been infected with Covid-19, which affect the purchase of organic vegetables, consumer preferences for the attributes of organic vegetables and the most important attributes for consumers. In deciding to buy organic vegetables in Surakarta City during the Covid-19 pandemic. The basic method is descriptive. The sample was determined by accidental sampling, and the city of Surakarta was deliberately chosen as the research location. The sampling technique used is accidental sampling. The data analysis method used is the method of multiple linear regression analysis, Chi-Square, and fishbein multi-attribute analysis methods. The results showed that the independent variables significantly affected the dependent variable together. Income variables, the number of family members infected with Covid-19, and the closest people infected with Covid-19 have a significant effect on purchasing organic vegetables in Surakarta City during the Covid-19 pandemic. Attributes of organic vegetables that have become consumer preferences during the covid-19 pandemic are good physical perfection where broad leaves do not have holes; freshness level is very fresh (<1 day), bright light green color, plastic packaging with the organic label, low price (<Rp. 10,000,-/package 200 grams), and medium-size (200-500 grams). The most important attribute in consumer considerations when deciding to buy organic vegetables, especially in Surakarta City during the Covid-19 pandemic, is the level of freshness. The order of attributes of organic vegetables from the most important to the least important is the level of freshness, physical perfection, packaging, color, price, and size.